Novel mutations in COX15 in a long surviving Leigh syndrome patient with cytochrome c oxidase deficiency. Issue 5 (29th April 2005) - Bugiani, M; Tiranti, V; Farina, L; Uziel, G; Zeviani, M
Abstract : Background: Isolated cytochrome c oxidase (COX) deficiency is usually associated with mutations in several factors involved in the biogenesis of COX. Methods: We describe a patient with atypical, long surviving Leigh syndrome carrying two novel mutations in the COX15 gene, which encodes an enzyme involved in the biosynthesis of heme A. Results: Only two COX15 mutated patients, one with severe neonatal cardiomyopathy, the other with rapidly fatal Leigh syndrome, have been described to date. In contrast, our patient had a slowly progressive course with no heart involvement. COX deficiency was mild in muscle and a normal amount of fully assembled COX was present in cultured fibroblasts. Conclusions: The clinical and biochemical phenotypes in COX15 defects are more heterogeneous than in other conditions associated with COX deficiency, such as mutations in SURF1 .